Socio-Cultural Sustainability and Attitude of Senior Secondary Students - Itasanmi, Babalola Stephen (NIU Journal of Social Sciences, 2020)
The global movement for the promotion of Education for Sustainable Development (ESD) dictates that more studies should be conducted on ways of teaching Sustainable Development (SD) concepts at all levels. This study investigated the attitude of junior secondary school students on element of sustainability, education for socio-cultural sustainability. The study adopted survey design. Respondents were randomly selected from five schools across Ijebu West Local Government of Ogun State, South West Nigeria. The instrument employed was Socio-Cultural Attitudes Questionnaire (SCAQ) with reliability of 0.75% using Cronbach coefficient alpha was used. Two hypotheses were tested at 0.05 level of significance using analysis of variance. The results revealed significant difference in the attitude of students to the concepts according to sex and school. The implication is that the disposition of students ton these concepts of socio-cultural sustainability varies according to sex and school. The study recommends that efforts should be intensified to develop the needful skills and orientation among learners for effective teaching and learning of socio-cultural sustainability. Keywords: Sustainable development, socio-cultural sustainability, education for sustainable development